Persepsi Pemahaman Pengusaha dalam Penyusunan Laporan Keuangan Berdasarkan SAK EMKM pada UMKM Kabupaten Jepara - Yanto Yanto (Jurnal Akuntansi dan Perpajakan, 2021)
The problem in developing Micro, Small and Medium Enterprises (MSMEs) is the lack of understanding of MSMEs in preparing financial reports based on SAK EMKM. The research aims to analyze information and socialization, education, length of business, and size of business to influence the understanding of MSMEs in preparing financial reports based on SAK EMKM. The research was conducted on 66 furniture MSME entrepreneurs in Jepara District. The research was conducted by distributing questionnaires and analyzed using multiple regression analysis and hypothesis testing t. The results showed that information and socialization had a significant positive effect on the preparation of financial statements based on SAK EMKM; education has a significant positive effect on the preparation of financial statements based on SAK EMKM; length of business has a significant positive effect on the preparation of financial statements based on SAK EMKM, and business size has a significant positive effect on the preparation of financial statements based on SAK EMKM.